Audit Reports on the Financial Statements of European Multinational Companies: A Comparative Study. - Hussein, Mohamed E. A. (The Accounting Review, 1991)
Abstract Reviews the book "Audit Reports on the Financial Statements of European Multinational Companies: A Comparative Study," by Simon Archer, Stuart McLeay and Jean-Bruno DuFour.